Sobre los derechos de la mujer en el fútbol profesional colombiano (2017)
"Women's football is an illustration of gender inequalities. Discrimination is presente In women's football as law wages, turf instead of natural grass and lack of media coverage." -- Tomado del Formato de Documento de Grado.